Self-Care Pedagogy in the Undergraduate Curriculum: A Post Pandemic Faculty Survey - Anya Y. Spector; Farah Reynoso (Journal of Human Services)
This exploratory study describes the post pandemic integration of classroom-based self-care pedagogy with students engaged in field placements in human services organizations. Forty-nine undergraduate faculty members at a large public university system in New York City completed an online survey about how they teach self-care (i.e., integrate self-care pedagogy) in their courses, their needs for resources, and barriers to integrating self-care. The survey is grounded in the National Organization of Human Services (NOHS) Ethical Standard 35, which requires human services workers to prioritize their own wellness and self-care. Burgeoning research demonstrates the deleterious effects of the Covid19 pandemic on undergraduate students' well-being. Students' difficulties are further exacerbated for those undertaking human services work in community-based organizations as student interns. Faculty recognized the mental health challenges faced by students in field placements, both because of the demands of agency-based human services work, as well as the exposure to sensitive classroom discussions about clients' psychosocial needs and traumas. However, most faculty have not meaningfully integrated self-care into the curriculum. This study highlights the need to develop strategies to promote student well-being and mitigate the effects of exposure to potential sources of vicarious trauma. Recommendations for best practices for undergraduate departments are offered.